Alternative prey mediate intraguild predation in the open field. Issue 9 (19th February 2022) - Snyder, Gretchen B; Smith, Olivia M; Chapman, Eric G; Crossley, Michael S; Crowder, David W; Fu, Zhen; Harwood, James D; Jensen, Andrew S; Krey, Karol L; Lynch, Christine A; Snyder, William E
Abstract: BACKGROUND: Generalist predators that kill and eat other natural enemies can weaken biological control. However, pest suppression can be disrupted even if actual intraguild predation is infrequent, if predators reduce their foraging to lower their risk of being killed. In turn, predator–predator interference might be frequent when few other prey are available, but less common when herbivorous and detritus‐feeding prey are plentiful. We used molecular gut‐content analysis to track consumption of the predatory bug Geocoris sp. by the larger intraguild predator Nabis sp ., in organic and conventional potato ( Solanum tuberosum ) fields. RESULTS: We found that higher densities of both aphids and thrips, two common herbivores, correlated with higher probability of detecting intraguild predation. Perhaps, Nabis foraging for these herbivores also encountered and ate more Geocoris . Surprisingly, likelihood of intraguild predation was not strongly linked to densities of either Nabis or Geocoris, or farming system, suggesting a greater importance for prey than predator community structure. Intriguingly, we found evidence that Geocoris fed more often on the detritus‐feeding fly Scaptomyza pallida with increasing predator evenness. This would be consistent with Geocoris shifting to greater foraging on the ground, where S. pallida would be relatively abundant, in the face of greater risk of intraguild predation. CONCLUSION: Overall, our findings suggest that while herbivorous prey may heighten intraguild predation of Geocoris in the foliage, detritivores might support a shift to safer foraging on the ground. This provides further evidence that prey abundance and diversity can act to either heighten or relax predator–predator interference, depending on prey species identity and predator behavior. © 2022 Society of Chemical Industry. Abstract : Intraguild predation of Geocoris by Nabis was more common in fields where aphids or thrips were more abundant.